Structural Changes in Brain MRI Associated with Psychogenic Functional Non-epileptic Seizures - Imran Khawaja (Research Developments in Medicine and Medical Science Vol. 1, 2023)
Psychogenic non-epileptic seizures (PNES) are a global health issue. They involve altered awareness, flaccid or stiff collapse, and tremulous limb motions. PNES are episodic functional neurological symptoms that seem like epileptic seizures but are not. PNES is one of the three most prevalent transitory loss of consciousness diagnoses. Neurologists see PNES most often as functional symptoms. PNES is usually misdiagnosed, resulting in the delay of appropriate psychological treatment. The study aimed to assess the structural changes in the brain in patients with PNES. This retrospective analytical cross-sectional study was conducted at the Department of Medicine and Neurology, Ayub Teaching hospital, Abbottabad, from October, 2020 to September, 2021. The medical records of 42 patients with confirmed PNES were gathered and reviewed retrospectively.The average age of the patients (standard deviation) was 34 (±9) years, and the average age at onset was 31.6 (±5.8) years. Three patients (7%) had a positive epilepsy family history. 24 (47.6%) patients with brain MRI scans reported abnormal findings, while 22 (52.4%) had normal imaging studies. The majority of patients with abnormal MRIs had white matter nonspecific changes (50%), Mesial temporal sclerosis (15%), and cysts (15%). Age at the beginning of PNES (p = 0.04), duration of PNES (p=0.01), concomitant epilepsy (p = 0.05), Generalized motor seizures (p= 0.03), and focal motor seizures (p= 0.02) were strongly linked with aberrant brain MRI findings. Patients with PNES have a higher-than-average prevalence of anatomical brain abnormalities. These findings support the growing evidence that PNES is a brain disorder rather than a medical mystery.